SALT-OVERLY SENSITIVE5 Mediates Arabidopsis Seed Coat Mucilage Adherence and Organization through Pectins . Issue 3 (7th May 2014) - Griffiths, Jonathan S.; Tsai, Allen Yi-Lun; Xue, Hui; Voiniciuc, Cătălin; Šola, Kre¡imir; Seifert, Georg J.; Mansfield, Shawn D.; Haughn, George W.
Abstract : A fasciclin-like arabinogalactan protein mediates Arabidopsis seed coat mucilage adherence primarily through its influence on pectin . Abstract: Interactions between cell wall polymers are critical for establishing cell wall integrity and cell-cell adhesion. Here, we exploit the Arabidopsis ( Arabidopsis thaliana ) seed coat mucilage system to examine cell wall polymer interactions. On hydration, seeds release an adherent mucilage layer strongly attached to the seed in addition to a nonadherent layer that can be removed by gentle agitation. Rhamnogalacturonan I (RG I ) is the primary component of adherent mucilage, with homogalacturonan, cellulose, and xyloglucan constituting minor components. Adherent mucilage contains rays composed of cellulose and pectin that extend above the center of each epidermal cell. CELLULOSE SYNTHASE5 ( CESA5 ) and the arabinogalactan protein SALT-OVERLY SENSITIVE5 ( SOS5 ) are required for mucilage adherence through unknown mechanisms. SOS 5 has been suggested to mediate adherence by influencing cellulose biosynthesis. We, therefore, investigated the relationship between SOS5 and CESA5 . cesa5-1 seeds show reduced cellulose, RG I, and ray size in adherent mucilage. In contrast, sos5-2 seeds have wild-type levels of cellulose but completely lack adherent RG I and rays. Thus, relative to each other, cesa5-1 has a greater effect on cellulose, whereas sos5-2 mainly affects pectin. The double mutant cesa5-1 sos5-2 has a much more severe loss of mucilage adherence, suggesting that SOS 5 and CESA 5 function independently. Double-mutant analyses with mutations in MUCILAGE MODIFIED2 and FLYING SAUCER1 that reduce mucilage release through pectin modification suggest that only SOS 5 influences pectin-mediated adherence. Together, these findings suggest that SOS 5 mediates adherence through pectins and does so independently of but in concert with cellulose synthesized by CESA 5.